Penerapan Cloud AI dalam Penyusunan Assessment For Learning - Listiyani, Listiyani; Cety Wahyu Muslimah; Asmah Kustati; Lilis Tri Fariyah; Agus Triwidodo; Purwono, Purwono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study describes the application of Cloud AI technology in the preparation of Assessment for Learning (AfL) in learning at State Islamic Senior High School (Madrasah Aliyah) in Magelang City, State Islamic Senior High School 3 in Sragen, State Islamic Senior High School 1 in Sragen, and State Islamic Senior High School in Sukoharjo, and identifies the challenges and efforts of teachers in its implementation. This research method uses a qualitative approach. The research subjects were teachers at State Islamic Senior High School (Madrasah Aliyah) in Magelang City, State Islamic Senior High School 3 in Sragen, State Islamic Senior High School 1 in Sragen, and State Islamic Senior High School in Sukoharjo. The informants of this study were teachers. Data collection techniques were interviews, observation, and documentation. The results showed that Cloud AI created a more systematic, fast, and data-driven formative assessment workflow. The process began with the analysis of learning objectives and competencies, followed by indicator mapping, and then the design of AfL instruments such as diagnostic quizzes, reflective questions, and formative assignments with the help of Cloud AI to be adaptive, varied, and support differentiated learning. Cloud AI also facilitates the real-time collection of AfL results through a cloud-based platform, including student answers, completion time, and error patterns, which are analyzed to identify misconceptions, gaps in understanding, and student learning progress. These findings enable teachers to provide rapid, meaningful, and personalized formative feedback, along with recommendations for remediation and enrichment. However, the implementation of Cloud AI still faces two main challenges: limited infrastructure and unequal digital access, and teachers' difficulty integrating AI analysis results into daily pedagogical practices in a contextual manner. Teachers' efforts to overcome these challenges include improving digital literacy and understanding of AI through ongoing training such as workshops, webinars, learning communities, and competency development programs. With the support of infrastructure and professional mentoring, Cloud AI has the potential to strengthen AfL's function in supporting student learning more effectively.